2009
DOI: 10.1002/ajpa.21168
|View full text |Cite
|
Sign up to set email alerts
|

Plant foods consumed by Pan: Exploring the variation of nutritional ecology across Africa

Abstract: It has been shown that differences in resource density and nutrient supply affect variation in ranging patterns, habitat use, and sociality. Among nonhuman primates, chimpanzees (Pan troglodytes) and bonobos (P. paniscus) have often been used as models for the link between social system and habitat ecology. Field reports suggest that resource density is higher in habitats occupied by bonobos (compared to chimpanzee habitats), and in the West (compared to the East) of the range of chimpanzees. In this study we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 55 publications
4
53
1
Order By: Relevance
“…Stems of F. mucuso are relatively abundant at Ngogo; each stem can produce an enormous fruit crop and might do so at any time of year (Watts et al, 2012b). The figs, which are relatively rich in fructose and glucose and have moderately high gross energy value (Hohmann et al, 2010; K. Potts, unpublished data), are the top food in terms of feeding time at Ngogo and a major staple food (Watts et al, 2012a), but are extremely rare at Kanyawara and a negligible part of the chimpanzee diet there. C. albidum is common at Ngogo but absent at Kanyawara.…”
Section: Discussionmentioning
confidence: 99%
“…Stems of F. mucuso are relatively abundant at Ngogo; each stem can produce an enormous fruit crop and might do so at any time of year (Watts et al, 2012b). The figs, which are relatively rich in fructose and glucose and have moderately high gross energy value (Hohmann et al, 2010; K. Potts, unpublished data), are the top food in terms of feeding time at Ngogo and a major staple food (Watts et al, 2012a), but are extremely rare at Kanyawara and a negligible part of the chimpanzee diet there. C. albidum is common at Ngogo but absent at Kanyawara.…”
Section: Discussionmentioning
confidence: 99%
“…The combined effects of diet and habitat selection lessen inter-specific competition for resources, thereby improving the opportunities for both gorillas and chimpanzees to maintain nutrient-rich diets [29], [30]. For example, gorillas are more terrestrial and larger than chimpanzees and will therefore exploit different food sources.…”
Section: Discussionmentioning
confidence: 99%
“…West African lowland gorillas and chimpanzees inhabit primary and old secondary forests; both consume mainly fruits complemented by vegetative matter [29][33] and small quantities of invertebrates [34][36]. Despite their overlapping diets, lowland gorillas are more selective in the choice of fruits than chimpanzees, but are more flexible when choosing non-fruit vegetative matter, especially during times of seasonal or annual fruit scarcity [37].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed information on diet composition of African apes is available from multiple sites (see publications in [47] and references therein). Although habitats vary in terms of nutritional ecology and although populations vary in terms of the type of plant foods they exploit [48], [49], the diet of bonobos and chimpanzees is similar in terms of the intake of nutrients and anti-feedants [49]. Chimpanzees prefer fruit which are high in sugar and low in tannin [50] and consumers maintain relatively high intake of fruit even at times of fruit scarcity [51].…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analyses of the nutritional content of plant foods consumed by the two Pan species revealed that chimpanzees focus on high energy sources such as fat, while bonobos have higher intakes of protein and non-structural carbohydrates including starch [47]. However, inclusion of information from other chimpanzee populations did not confirm this pattern making the intake of starch by the two Pan species more similar [49].…”
Section: Discussionmentioning
confidence: 99%